Personality disorder : temperament or trauma? : an account of an emancipatory research study carried out by service users diagnosed with personality disorder /: temperament or trauma? : an account of an emancipatory research study carried out by service users diagnosed with personality disorder. (2008) - Unknown
No abstract available